2016
DOI: 10.1039/c6ra15638j
|View full text |Cite
|
Sign up to set email alerts
|

A practical and efficient synthesis of methyl levulinate from cellulosic biomass catalyzed by an aluminum-based mixed acid catalyst system

Abstract: A combination of aluminum compounds and organic sulfonic acids was an efficient catalyst system for direct methyl levulinate synthesis from both microcrystalline cellulose and wood powder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 48 publications
0
19
0
Order By: Relevance
“…Isomerization of glucose to fructose could be achieved using biological or chemical catalysts including homogeneous base/acid catalysts or heterogeneous solid catalysts . Many types of research contributed to the acid-catalyzed isomerization of d -glucose to d -fructose promoted by aluminum-based catalysts. , Ekeberg et al reported that the addition of aluminum oxide to a boiling solution of glucose-containing pyridine leads to a significantly higher reaction rate of the aldose–ketose transformation and it showed a substantially higher yield of fructose (50%) compared with the classical Lobry de Bruyn–Alberda–van Ekenstein transformation . In order to increase the yield of fructose, the hydroxide-containing resin was further modified with sodium aluminate to obtain a resin-bound aluminate …”
Section: Introductionmentioning
confidence: 99%
“…Isomerization of glucose to fructose could be achieved using biological or chemical catalysts including homogeneous base/acid catalysts or heterogeneous solid catalysts . Many types of research contributed to the acid-catalyzed isomerization of d -glucose to d -fructose promoted by aluminum-based catalysts. , Ekeberg et al reported that the addition of aluminum oxide to a boiling solution of glucose-containing pyridine leads to a significantly higher reaction rate of the aldose–ketose transformation and it showed a substantially higher yield of fructose (50%) compared with the classical Lobry de Bruyn–Alberda–van Ekenstein transformation . In order to increase the yield of fructose, the hydroxide-containing resin was further modified with sodium aluminate to obtain a resin-bound aluminate …”
Section: Introductionmentioning
confidence: 99%
“…The direct production of alkyl levulinates from glucose could be achieved using catalysts having both base and acid sites [6] or Lewis and Brønsted acidic functionalities [7]. Methyl levulinate can be efficiently obtained from pure sugars and lignocellulosic biomasses by combining aluminum salts and organic sulfonic acids [8]. EL could also be proficiently produced by combining iron and aluminum salts with sulfuric acids under relatively mild conditions (T > 453 K).…”
Section: Introductionmentioning
confidence: 99%
“…Tominaga and Ding also both reported that acid catalysts containing Lewis and Brønsted acid sites exhibit better catalytic activity for cellulose. 13,14 Phem et al 15 showed that a Brønsted acid was able to catalyze the hydrolysis of cellulose to glucose and the dehydration of fructose to 5HMF, while a Lewis acid catalyzed the isomerization of fructose to glucosides. Ding et al 14 synthesized a niobium-based phosphate (NBPPH1) catalyst with double acid sites for the production of methyl levulinate (ML) from cellulose in methanol and obtained 96% cellulose conversion and a 56 mol% yield after 24 h at 180 °C.…”
Section: Introductionmentioning
confidence: 99%